Competitive Advantage Strategy To Increase Sales of PT ABC'S Layer Feed - Irzandi, Uray; Jahroh, Siti; Djohar, Setiadi (School of Business, IPB University (SB-IPB), 2024)
In Indonesia, the potential demand for eggs was still high from time to time reaching 5.2 million tons in 2021, triggering every animal feed company to compete in providing the national demand for eggs. PT ABC was one of the animal feed mills that experienced a decline in market share of 1.92% in 2021. This paper aims to identify the factors influence product competitive advantage, analyze internal and external factors, and formulate strategies to increase market share. Data was analyzed using IFE, EFE, IE, and SWOT matrix and ended with QSPM to get priority strategies from December 2022 until January 2023. The highest competitive advantage factor at PT ABC was in the after-sales service to customers with the highest priority strategy for the development of products to increase market share was increasing feed production while maintaining quality and the market penetration strategy was strengthening cooperation with third parties to facilitate business. Two priority strategies could be implemented for PT ABC. First on the product development strategy to increase feed production while maintaining quality and strategy regarding market penetration was sales segmentation to retail traders and direct breeders. Keywords: after sales, eggs, feed production, qspm, swot